RETRACTED: Revealing the Effects of Corporate Governance on Green Investment and Innovation: Do Law and Policy Matter? - Lai, Yuan; Sohail, Muhammad Tayyab (Frontiers in Psychology, 2022)
Green investment and innovation performance are key factors of sustainable green development. Green investment and innovation have become a trendy solutions to minimize environmental issues in the previous few decades. We investigate the effects of corporate governance, environmental law, and environmental policy stringency on green investment and environmental innovation using Chinese time-series data from 1998 to 2020. Short and long-run findings indicate that corporate governance has a positive and significant impact on green investment and innovation in China. However, environmental law has positive and significant effects on green investment and innovation in the short-run and long-run. Furthermore, environmental policy stringency has an insignificant impact on green investment but stimulates green innovation in the short and long-run. The study also reveals that education has a significant positive impact on green innovation in short-run and long-run. The short and long-run results propose essential policy implications.